Вимоги до експерта-релігієзнавця у сфері наукової експертизи - Колосок, Тетяна Святославівна; Колосок, Татьяна Святославовна; Kolosok, Tetiana S. (Східноєвропейський національний університет імені Лесі Українки, 2014)
Релігія завжди відігравала значну роль у суспільно-політичних процесах, була та є важливим фактором світової політики й, на жаль, – причиною конфліктів, що, відповідно, актуалізує пошук новітніх шляхів урегулювання міжконфесійних відносин, одним із яких є релігієзнавча експертиза. Значимий аспект цієї проблематики – питання статусу експертів, їхньої професійної компетентності. З’ясовано, що релігієзнавчу експертизу можуть здійснювати незалежні експерти-релігієзнавці, які повинні мати вищу освіту, учений ступінь кандидата або доктора наук у сфері релігієзнавства, досвід професійної діяльності. У статті розкрито сутність принципів, якими повинні керуватись експерти, виконуючи релігієзнавчу експертизу (дотримання права на свободу совісті й свободу віросповідання, принципами незалежності експерта, об’єктивності, усебічності, комплексності). Saturation of religious space by religious associations, complicated relations between certain confessions, insubstantial accusations and commitment, actualize searching of the newest ways for interconfessional relations settlement, one of which is religious studies examination. One of the meaningful aspects of the problems range for religious studies examination realization is the question of experts’ status, their professional competence. The aim of the article is analysis of requirements to the expert student of religion in realization of scientific examination. Legal framework of religious studies examination are the norms of the Law of Ukraine Law of Ukraine «On the right of conscience and religious organizations», and besides, from 1995 in Ukraine the Law on scientific and scientific-technical examination (with additions made in 1999, 2006 and 2012) acts, which determines legal, organizational and financial frameworks of the expert activity in scientific and scientific-technical sphere. However, in this Law nothing is said concerning religious studies examination, although it is logical to assume that it is the variety of scientific examination. While research it was found out by us, that the experts in the sphere of religious studies could not be public organizations, citizens being in contractual relationships with any religious organization, government employees, priests, professional theologians. We agree with the opinion of both home and foreign leading theoretical scientists and practical scientists, lawyers, that religious studies examination should be conducted by independent religious expert scientists, who should have higher academic/ secular education, qualification confirmed by the graduate degree of Candidate or Doctor of sciences in the sphere of religious studies; experience of successful and versatile professional activity, competence in a certain subject sphere, close in relation to the expertise object. Carrying out religious studies examination, experts should follow the principles of observance the right on the right of conscience and religious freedom, principles of the expert independence, objectivity, research comprehensiveness and plenitude, complexity and competence. Requirements to qualification of expert student of religion in Ukraine are not envisaged legislatively, unfortunately, there is no special preparation of expert student of religion, that is why we think it reasonable to create conditions for passing the special educational training for future expert student of religion.
Requirements to an Expert Student of Religion in the Sphere of Scientific Examination
Keywords: релігієзнавча екпертиза; експерт-релігієзнавець; міжконфесійні відносини; religious studies examination; expert student of religion; interconfessional relations